(untitled) (Revista Apotheke, 2020)
Experience is one determining factors in obtaining new knowledge. The use of the poetic process as a teaching strategy provides meaningful and transformative learning experiences, breaking with the dichotomy between theory and practice. This text presents the results of a study that used the curricular component Painting as a research field, from the Visual Arts Degree course, which was held in the Unochapecó painting studio, during the first semester of 2019. The teaching dynamics used revealed a enlargement of the atelier’s functionalities, perceived as a space for teaching, production and exhibition, showing its relevance in the teacher-artists’s formation. The teaching methodology used was structured in four problem situations: Poetic production; Simulation and dialogue; Assembly of the portfolio; Exhibition. The studio was experienced and analyzed as a space for teaching experiences, being marked by the student’s role, based on the development of skills and not on the content transmission.